2014
DOI: 10.1016/j.ijhydene.2014.05.141
|View full text |Cite
|
Sign up to set email alerts
|

Ignited releases of liquid hydrogen: Safety considerations of thermal and overpressure effects

Abstract: a b s t r a c tIf the 'Hydrogen Economy' is to progress, more hydrogen fuelling stations are required. In the short term and in the absence of a hydrogen distribution network, these fuelling stations will have to be supplied by liquid hydrogen (LH2) road tankers. Such a development will increase the number of tanker offloading operations significantly and these may need to be performed in close proximity to the general public.The aim of this work was to determine the hazards and severity of a realistic ignited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Much work is required to better define the parameters effects especially under variable environmental conditions. Work has also increasingly looked at medium to large scale ignition experiments [17] [18] [19], and modelling and validation of complex scenarios using computational fluid dynamics [17] [20] but further work is needed to explore this fully on the ground, and in air profile conditions, especially in order to validate modelling. Brewer determines that in a series of large-scale release experiments no evidence of detonation could be found, and that pressure effects from a fireball were negligible when unconfined, however turbulence and obstacles/ geometry may play a key role in worsening this action [19].…”
Section: Flammable Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work is required to better define the parameters effects especially under variable environmental conditions. Work has also increasingly looked at medium to large scale ignition experiments [17] [18] [19], and modelling and validation of complex scenarios using computational fluid dynamics [17] [20] but further work is needed to explore this fully on the ground, and in air profile conditions, especially in order to validate modelling. Brewer determines that in a series of large-scale release experiments no evidence of detonation could be found, and that pressure effects from a fireball were negligible when unconfined, however turbulence and obstacles/ geometry may play a key role in worsening this action [19].…”
Section: Flammable Hazardsmentioning
confidence: 99%
“…Modelling of hydrogen using FLACS has been well developed [23] but the understanding of leaks, dispersion and ignition/ fire/ explosion events under varying environmental conditions, particularly for large scale releases, have not been validated to any great degree as only limited experimental work has been performed in this area with specific release rates [19].…”
Section: Flammable Hazardsmentioning
confidence: 99%
“…Off-site stations are the most common type throughout the world and have had several safety issues, which have been investigated. For example, the leakage and dispersion of compressed or liquified hydrogen have been analyzed both experimentally and using simulations [3,4]. Further, consequence analysis and risk assessment studies of off-site hydrogen fueling stations have been performed to determine the necessary safety measures [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These include two-phase releases, dispersion of cryogenic and LH 2 in enclosures, physical properties of LH 2 , effect of turbulence and, buoyancy on heat transfer between cold hydrogen and ambient air and experiments that can provide a closure to these issues. Hall et al [7], reported experimental studies to establish the severity of an ignition from a release of LH 2, with spill rates consistent with a transfer hose operation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the radiation heat flux measurements they created a safety distance guide which only corresponds to their hydrogen spillage rate. While these and several other large scale studies have looked at the pooling and vaporization of hydrogen [4][5][6][7][8], these experiments are sparsely instrumented with poor control of some boundary conditions. Accordingly, there is the risk that the use of improperly validated models to establish safety envelopes could be detrimental to the emergence of hydrogen as a transportation fuel.…”
Section: Introductionmentioning
confidence: 99%